El Carmen de Bolívar: a lesson not to be forgotten - Carlos Fernando Grillo-Ardila (Revista Colombiana de Obstetricia y Ginecología, 2014)
The growing concern regarding the safety of vaccination against human papillomavirus (HPV) is no secret to anyone in Colombia.